Understanding Higher Education EFL Learners’ Motivation in Southeast Asia Context: A Systematic Literature Review - Janah, Miftahul; Widiati, Utami; Fitriyah, Ima (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Motivation is regarded as one of the major factors in language learning. Therefore, it is very important for teachers to recognize and foster individual students’ motivation as well as identify and respond to their concerns. This systematic literature review study aimed to portray students’ motivational level, orientation, and factors that are dominantly affecting motivation among higher education students in the Southeast Asia context. There are two stages comprised in this study—selecting the pool of review studies and discussing the outcomes of the review. Having thorough sorting and eliminating irrelevant and duplicate articles from three databases (Sciencedirect, ProQuest and ERIC), 15 articles derived from Indonesia, Thailand and East Timor were finally selected. This study, then, found that students’ motivational levels were generally high, and they were more extrinsically than intrinsically motivated, in which most students learn English for their future better job (careers). It was reported that the key factors motivated students in the learning process were friends, and teachers (personality, competence, teaching method), and somehow female students have a different motivational level and orientation from male students. Hence, the English teachers are suggested to reconsider using a method or anything which can improve students’ motivation for both female and male students, both extrinsically and intrinsically. further studies are recommended to include a broader search database and also area part of countries.